High endemicity of Clonorchis sinensis infection in Binyang County, southern China. - Junling Sun; Hualei Xin; Zhihua Jiang; Menbao Qian; Kaixia Duan; Yingdan Chen; Shizhu Li; Wei Li; Shiyong Huang; Xiaoqin Gan; Yichao Yang; Zhongjie Li (Public Library of Science (PLoS), 2020)
High-intensity clonorchiasis infection is associated with serious outcomes, including cancer. Understanding the infection intensity of Clonorchis sinensis and its risk factors in local endemic regions could facilitate effective control measures. In a county located in a highly endemic area in Guangxi Province, P. R. China, local residents were randomly enrolled in the study; helminth egg examinations were performed with the Kato-Katz method, and the intensity of infection was identified as mild, moderate or heavy. Knowledge, attitudes, and high-risk behaviours were investigated among those infected with Clonorchis sinensis. A total of 2521 local residents participated in this study, and the Clonorchis sinensis-positive proportion was 28.9% (728 persons). Among the infected persons, the percentages of mild, moderate and heavy infections were 66.2%, 28.4% and 5.4%, respectively. Males experienced a higher proportion of moderate and heavy infections (37.5%) than females (18.1%) (p<0.05). The highest infection proportion among the different levels of infection intensity was identified among persons aged 30-59 years (15.7% for moderate and heavy infections). Among the 509 persons who reported eating raw fish, 302 persons (59.3%) had eaten raw fresh fish for more than 10 years, and 131 (25.7%) persons ate raw fish ≥12 times a year. Multivariate logistic regression revealed that eating raw fish 12-50 times in the last year (adjusted odds ratio [aOR] = 1.74, 95%CI: 1.09-2.80) and eating raw fish >50 times in the last year (aOR = 2.89, 95%CI: 1.20-7.50) were risk factors for high-intensity infections (moderate and heavy). The overall infection proportion was high in the study area, with a large group of residents experiencing high-intensity infections. High frequency of raw fish consumption was associated with high-intensity infections. Intervention strategies targeting people with a high frequency of raw fish consumption should be implemented to reduce the probability of severe consequences.